Analisis Komparatif Pembiayaan MMQ dan KPR Konvensional - Ina Naila Sakinah; Sherli Ramadhani; Alfiyah Salwa Azizah; Muh Furqan Al Faruqi; Kamaruddin Kamaruddin (LPPM Universitas Sains dan Teknologi Komputer, 2025)
Musyarakah Mutanaqisah (MMQ) is a form of sharia-based financing that offers a home ownership solution free from elements of interest (riba). This article aims to analyze the application of the MMQ contract in housing finance, compare it with the conventional mortgage scheme (Kredit Pemilikan Rumah/KPR), and evaluate its impact on community welfare. This study employs a descriptive qualitative approach through literature review of academic sources, regulations, and other relevant data. The analysis shows that MMQ is superior in terms of compliance with Islamic principles, fairness in risk sharing, and flexibility in payment structure. Furthermore, the MMQ scheme contributes to the improvement of social and economic well-being, particularly for the lower-middleincome segment of society. Nevertheless, its implementation still faces challenges such as the risk of default and the need for strengthened risk management systems. Therefore, collaboration between Islamic financial j, the government, and the public is essential to optimize the potential of MMQ as a fair and sustainable alternative for home financing